1999
DOI: 10.1053/hn.1999.v120.a83517
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologic Features of Laurence‐Moon‐Bardet‐Biedl Syndrome

Abstract: The most common otolaryngologic features associated with LMBBS include SNHL, speech and language disorders, and oral and dental abnormalities. Early otolaryngologic, audiologic, speech pathology, and dental evaluation of these individuals is recommended. This is the first reported case of bifid epiglottis, a rare congenital laryngeal anomaly, found in association with LMBBS. Most patients with bifid epiglottis have additional congenital anomalies, most commonly polysyndactyly. Polysyndactyly is a feature of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 15 publications
1
33
1
Order By: Relevance
“…In contrast to the cases reported previously [Urben and Baugh, 1999], only one of the subjects reported here with bifid epiglottis had symptoms referable to the larynx. None of our subjects reported symptoms of aspiration or phonation abnormalities, and only one patient reported dysphagia, which may not be related to the epiglottic cleft.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the cases reported previously [Urben and Baugh, 1999], only one of the subjects reported here with bifid epiglottis had symptoms referable to the larynx. None of our subjects reported symptoms of aspiration or phonation abnormalities, and only one patient reported dysphagia, which may not be related to the epiglottic cleft.…”
Section: Discussioncontrasting
confidence: 99%
“…More than half of the PHS subjects (16 of 27) had a malformation of the epiglottis, most commonly a completely or partially bifid epiglottis. This frequency is remarkable because of the rarity of bifid epiglottis [Urben and Baugh, 1999]. The number of subjects with epiglottic clefting in this study is comparable with the number identified in the entire literature prior to this report.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to retinitis pigmentosa, strabismus may be observed [7]. Early otolaryngologic, audiologic, speech pathology, and dental evaluation of these individuals is recommended [8]. Bifid epiglottis [8] and disturbance of tooth formation have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early otolaryngologic, audiologic, speech pathology, and dental evaluation of these individuals is recommended [8]. Bifid epiglottis [8] and disturbance of tooth formation have been reported. Hypertrophy of the interventricular septum and dilated cardiomyopathy, insulin-resistant diabetes mellitus, empty sella, clinodactyly, and congenital hepatic fibrosis can also be found.…”
Section: Introductionmentioning
confidence: 99%